KEBIJAKAN KERAJAAN DAN PERTUMBUHAN INDUSTRI PERIKANAN DI SELAT MALAKA SEBELUM PENJAJAHAN - Azmi Fitrisia (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
This paper aims to prove the relation of Siak Kingdom policy to fishery industry in Malacca Strait. Because the Strait Malacca have rich by fishes. The archeologis fact eksplans many of clem shell of wasting of the coastal communities wastes. The question research is how relation of the Siak Kingdom policy to fishery before colonialism? How was the develop of fishery industry in Rokan estuary?. Historical method was used to the research. The primery dan secondary data was met from local, Netherlands and England archives. Second, eksternal and internal critic. It uses for checking truth of the data. All of the fact is interpretated and be related to get the conclution. The result of the research is there was not Siak kingdom policy to fishery. The fishery developted manually depend economic insting of society. Bengkalis was poppulis than Rokan estuary-Bagan Siapi api. The Bengkalis was biggest place of fishery in South East Asia before colonialism. Bengkalis was popular with eggs and terubuk fishes. Many of poem had tell about popularity of the terubuk fishes as likes poem of